SANKSI HUKUM MENDIRIKAN BANGUNAN TANPA IZIN DIATAS TANAH HAK MILIK ORANG LAIN - Herry Hendri Fernando Mote; Salvadoris Pieter (Jurnal Restorative Justice, 2022)
Abstract Fulfilling the need for land is a basic right for every human being, which is passed down from generation to generation. Besides land having economic value it also has a social function, therefore it is certain that every person or community group will defend the land they own in various ways if someone threatens or disturbs their land ownership. The importance of land is so that the Government makes regulations that can be used in resolving land conflicts experienced by the community, to give a deterrent effect to violators. This research is a normative research using a statutory approach, historical approach, and conceptual approach. From these problems it can be concluded that there are various rules that can be used in imposing sanctions on violators who use land without permission from the rightful party. As for the causes of violations of land use without permission, those who are entitled to land are motivated by the necessity of life, so that they are compelled to commit acts that violate the law. Keywords: Legal Sanctions, Property Rights, Land.